2004
DOI: 10.1042/bst0320421
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis

Abstract: Anoikis is apoptosis induced by loss of cell adhesion or inappropriate cell adhesion. Adhesion on the extracellular matrix is important to determine whether a cell is in the correct location and to delete displaced cells by apoptosis. The ability to overcome this requirement has important implications for metastatic cancer. However, how adhesion signals are interpreted by a cell into a life or death decision is complex. In this paper, we will examine this from the point of view of the apoptotic machinery of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 49 publications
5
91
0
1
Order By: Relevance
“…1H), E-cadherin, and N-cadherin; it was never detected in engrafted cells expressing junctional and adhesion proteins. This phenomenon is consistent with anoikis of the nonengrafted cells, which is one of the aspects of programmed cell death triggered by the lack of cell-to-cell contacts (8). Quantitative measurements at 2 days showed that only Ϸ5% (4,800 Ϯ 2,600) of the 80,000 -100,000 injected nonactivated CPCs were present in the myocardium whereas Ϸ50% (48,000 Ϯ 18,000) of activated CPCs were detected.…”
Section: Cpc Survival and Engraftmentsupporting
confidence: 54%
“…1H), E-cadherin, and N-cadherin; it was never detected in engrafted cells expressing junctional and adhesion proteins. This phenomenon is consistent with anoikis of the nonengrafted cells, which is one of the aspects of programmed cell death triggered by the lack of cell-to-cell contacts (8). Quantitative measurements at 2 days showed that only Ϸ5% (4,800 Ϯ 2,600) of the 80,000 -100,000 injected nonactivated CPCs were present in the myocardium whereas Ϸ50% (48,000 Ϯ 18,000) of activated CPCs were detected.…”
Section: Cpc Survival and Engraftmentsupporting
confidence: 54%
“…Anoikis, apoptotic cell death due to loss of cell adhesion, is critical for regulation of tissue homeostasis in tissue remodeling, development, fibrosis and tumor metastasis (Valentijn et al, 2004). Here, we showed that decreased CRT was associated with increase of anoikis in ESCC cells.…”
Section: Discussionmentioning
confidence: 68%
“…10,11 The physiological relevance of anoikis has been confirmed by the fact that cancer cell lines, rather than normal epithelial cells, are usually not sensitive to anoikis and many have developed anchorage independence, which means that they do not require adhesion to ECM for proliferation and survival. [12][13][14][15] Anoikis has also been suggested to act as a physiological barrier to metastasis, and anoikis suppression is the first step taken by metastatic cells. 16 Hepatocyte growth factor (HGF) mediates tumor-stromal interactions that confer invasive, angiogenic and metastatic potential to various cancers through HGF/c-Met receptor binding.…”
mentioning
confidence: 99%